Novel Approach for 2-Port Laparoscopic Hysterectomy. (August 2019) - Tyan, Paul; Robinson, James; Dandapani, Monica; Li, Jessica; Gu, Alex; Moawad, Gaby N.
Background and Objectives . To describe a novel technique for a port-reducing laparoscopic hysterectomy. The 2-port laparoscopic hysterectomy (TPH) is performed through two 5-mm ports without the use of any multiport channels. We demonstrate outcomes via a large case series. We also describe and provide a video showing the TPH technique. Methods . Retrospective comparative study between the newly developed TPH and the conventional 4-port hysterectomy techniques. Variables of patients who underwent a TPH with fellowship-trained gynecologic surgeons at a single academic university hospital were collected through electronic medical records chart review. Results . Forty-five patients underwent a TPH. Mean age was 39.4, body mass index was 28.5 kg/m 2, and uterine weight was 170.0 g. Our outcomes of interest were operative time (98.4 minutes, mean), estimated blood loss (65.6 mL, mean), conversion to 3-port (1/45), and intraoperative (0/45) and postoperative (5/45) complications. By comparing the TPH to the conventional 4-port laparoscopic hysterectomy within a similar setting, we provide insight into variables that prompt the minimally invasive gynecologic surgeon to perform a port-reducing procedure. Patients were more likely to be allocated for a TPH if they were younger (37.8 vs 44.7, P = .005), had a lower body mass index (29.0 vs 32.5, P = .07), smaller uterus (143.1 vs 672.3 g, P < .001), and were white (56.8% and 22.4%, P < .001). Conclusions . The TPH is a novel port-reducing hysterectomy that is safe in a subset of patients with small uteri and limited surgical history who require no other surgical interventions at the time of hysterectomy.